Prague and Central Bohemia : Current Population Processes and Socio-Spatial Differentiation. - Ouředníček, Martin (Karolinum Press, 2022)
The theme of socio-spatial differentiation has belonged to the core issues of social geography and urban studies for a long time. The general aim of the book is to describe and explain the current socio-spatial differentiation of Prague and the Central Bohemian Region and the processes that have influenced it during the first two decades of the twenty-first century. The book offers its own theoretical perspective on the structuration of spatial patterns and the social environment, a general view of regional development, and the main socio-spatial processes of the period after transition. Maps are an important part of this volume and concentrate crucial information within most chapters. Apart from the static information described in the maps, the book offers a look at current population "processes", as hinted at by the subtitle of the publication. The presentation and evaluation of "processes" require more dynamic forms of cartographic visualisation and new methods of investigation. Among them, new tools of segregation measurement, various approaches for the use of mobile phone data, and an innovative form of population forecast are presented in the book. The common thread connecting all chapters is a regional focus on Prague and the Central Bohemian Region and a quantitative approach to comparing spatial patterns and regional processes.